Emotion characteristics of older adults with MCI among a socially isolated cohort using NIH toolbox: I‐CONECT Study. (31st December 2021) - Yu, Kexin; Wild, Katherine; Silbert, Lisa C; Kaye, Jeffrey A; Dodge, Hiroko H
Abstract: Background: A diagnosis of Mild Cognitive Impairment (MCI) has been found to be associated with changes in emotional wellbeing and social relationships. Socially isolated older adults with MCI are at greater risk of developing Alzheimer's Disease and Related Dementias. Better understanding the emotional functioning of individuals with MCI could inform the development of behavioral health interventions. Within a socially isolated sample of older adults, this study compares psychosocial wellbeing of older adults with MCI to their cognitively normal counterparts. Methods: This cross‐sectional study uses baseline data from the Internet‐based Conversational Engagement Clinical Trial (I‐CONECT, ClinicalTrials.gov: NCT02871921). Eligible participants were ages 75 or older and were socially isolated as defined by scoring <12 on the 6‐item Lubben Social Network Scale, engaging in conversations lasting 30 minutes ≦ twice per week, or answering "Often" to at least one question of the three‐item UCLA Loneliness Scale. MCI status was determined according to clinical diagnosis. This working sample includes the first 127 participants whose baseline emotion battery scores were available as of November 2020. Based on NIH Toolbox scoring instructions, three domain scores were calculated with the 17 emotion measures, i.e., negative affect, social satisfaction, and psychological wellbeing. Linear regressions were conducted for all 17 Emotion Battery measures and 3 domain scores, controlling for age, gender, education, and severe depressive symptoms. Severe depressive symptom was operationalized as scored ≧5 on the 15‐item Geriatric Depression Scale (GDS). Results: Participants' mean age was 81.1 (SD=4.6); 69.9% of the participants were female; and mean years of education was 15.2 (SD=2.3). 54% of the participants were diagnosed with MCI. The average GDS score was 2.3 (SD=1.8). For the three major emotion domains assessed, older adults with MCI had more negative affect, yet no difference was observed in social satisfaction and psychological wellbeing (see Table 2). More specifically, compared to cognitively normal older adults, individuals with MCI had higher levels of fear, perceived hostility, perceived stress, sadness, and lower self‐efficacy. Conclusion: The study's findings indicate that older adults with MCI experience more negative emotions than cognitively normal older adults. However, there were no between‐group differences observed in positive emotions.